A retrospective report on xenotransfusion of canine serum albumin in five critically ill cats - Sirabian, Eric; Walton, Rebecca A.; Blong, April E. (Frontiers in Veterinary Science, 2025)
This retrospective case series describes the xenotransfusion of canine serum albumin (CSA) in five critically ill cats. Four cats received a single xenotransfusion of CSA, while one cat received two separate xenotransfusions. Overall, two out of five cats (40%) survived long enough to be discharged, which is similar to previously published survival rates for critically ill cats. One cat exhibited clinical signs attributable to acute transfusion-associated circulatory overload (TACO), while two cats showed clinical signs suggestive of a possible, although less likely, transfusion reaction. While a prospective study is needed, the review of the cases presented here suggests that CSA may provide oncotic and hemodynamic support and be safe to administer to critically ill cats.